Watering, renal physiology and control of water loss - Nicholson, M.J. (International Livestock Centre for Africa, 1983)
Discusses water requirements & intake and renal physiology in cattle, esp. those kept by Borana pastoralists in Ethiopia, in relation to some of the issues raised by JEPSS Research Memorandum no. 1.